ALCOHOL CONSUMPTION AND RISK FOR PARKINSON'S DISEASE : A SYSTEMATIC REVIEW - BrGirsang, Dr. Lora Coarnita (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
The neurodegenerative disorder known as Parkinson disease (PD) is an illness that affects the brain. It is characterized by motor symptoms such as sluggish movement, tremor, stiffness, and imbalance, as well as other consequences such as cognitive impairment, mental health issues, sleep difficulties, and pain and sensory abnormalities. It is also characterized by additional complications. Over the course of many decades, lifestyle exposures such as smoking, drinking coffee or tea, and consuming alcohol have been the subject of study, and the findings have been variable and sometimes contradictory. Lifestyle exposures such as these have been identified as contributing factors to the risk of Parkinson's disease (PD), in addition to the genetic and familial environmental exposures that are often stated as contributing factors to the risk of the illness. Alcohol consumption has been linked to Parkinson's disease (PD), although the biochemical mechanisms behind this connection are poorly understood and open to conjecture. The fact that we identified different correlations with different types of alcoholic beverages led us to infer that the mechanisms at play involve components that are not the ethanol itself or that are in addition to it. Beer, but not wine or liquor, contains a significant amount of purine, which, when mixed with ethanol, has the ability to enhance plasma urate levels in a synergistic way. Wine and liquor, on the other hand, do not include purine. However, data regarding the relationship between alcohol consumption and PD are inconsistent.